2020
DOI: 10.29399/npa.26148
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) from the point of view of Neurologists: Consideration of Neurological Findings and Symptoms during the Combat against a Pandemic

Abstract: Some respiratory viruses have long been known to cause neurological involvement. A novel coronavirus, leading to severe acute respiratory syndrome, also called coronavirus disease 19 (COVID-19), seems to be a new member of neuroinvasive viruses. While severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) keeps on spreading around the world rapidly, reports about the neurological manifestations associated with SARS-CoV-2, increases day by day. It is reported that a variety of symptoms and syndromes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…There are some studies and reviews highlighting that the most common neurological symptom is headache, often accompanied by high fever, moreover headache can occasionally be seen alone as the first sign of the disease [2,7]. A recent meta-analysis reported that the prevalence of headache was 10.9% with a high level of heterogeneity [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies and reviews highlighting that the most common neurological symptom is headache, often accompanied by high fever, moreover headache can occasionally be seen alone as the first sign of the disease [2,7]. A recent meta-analysis reported that the prevalence of headache was 10.9% with a high level of heterogeneity [8].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] To date, there are some studies and reviews highlighting that the most common neurological symptom is headache, often accompanied by high fever, whereas headache can occasionally be seen alone as the rst sign of the disease. 2,6 Therefore, detailed questioning of the presence of headaches in patients who admitted to the emergency and outpatient departments is still an important step in the prompt recognition of the infection in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a variety of symptoms and syndromes such as headache, dizziness, confusion, ataxia, epilepsy, ischemic stroke, neuropathic pain, and myopathy are common especially in more severe coronavirus disease-2019 (COVID-19) patients. 1,2 SARS-CoV-2 may cause headache symptoms through direct or indirect mechanisms 3 and could be a new member of neuroinvasive viruses due to the complex nature of the inflammation. 1 Surprisingly, the risk factors and comorbid disorders of COVID-19 are somewhat different from other respiratory viral illnesses.…”
Section: Introductionmentioning
confidence: 99%